Petrology of Diorites from The "Kohistan Sequence'', Swat, Northern Pakistan. A Genetic Interpretation at Plate Scale - Majid, M. (Journal of Himalayan Earth Sciences, 1979)
Diorites and related rocks of the cabalkaline nature include by far the most dominant rocks of various composite plutons extensively distributed within the suture zone in the Kohistan Himalayas in northern Pakistan. The main Himalayan suture zone has been recently traced across Kohistan through the Districts of Hazara, Swat, Dir and Mohmand by Tahirkheli et al. (1979). The development of the thick complex of various types of diorite, granodiorite, hypersthene gabbro and calc-alkaline volcanics (andesite-dacite-rhyolite) within the suture zone in Kohistan is unique in nature because along the Tsang Po and Tndus valley in the east, the suture zone is characterized by a belt of flysch and volcanics with some ophiolitcs and "melanges" (Ganaer, 1964, 1977) and to the west in Afghanistan it is marked by large "napper" of typical ophiolitic rocks. In a tectonic discussion of the Kohistan area it has been pointed out that igneous rocks within the "Kohistan Sequence" represent products of calc-alkaline activity, associated with the subduction of the floor of the former Tethyne ocean under a marginal basin. The mineralogical and chemical constraints of the diorites and related rocks described in this paper from the galam area (between latitude 35' 15' to 35" 52' N and longitude 72" 20' to 72" 27' E) favour the possibility of their derivation as a result of the active consumption of the oceanic crust dragged beneath the marginal basin while the concentra means an intrusive. The M.M.T. is dearly observable in areas south of Patan and can be traced to the west through Shangla Pass across the Swat valley near Khwazakhela and the Dir valley at Zullum.